Stereoselective synthesis. - Rahman, Atta-ur-, 1942- (Studies in natural products chemistry ;, 1993)
Studies in Natural Products Chemistry Volume 12: Stereoselective Synthesis (Part H) reviews the stereoselective synthetic and mechanistic chemistry of bicyclomycin. It discusses chemical studies of the taxane diterpenes; the synthetic methodology for 2-amino alcohols of biological interest; and the synthesis and structure of hydroxylated indolizidines. Some of the topics covered in the book are the synthetic routes to the oxahydrindene subunit of the avermectin-milbemycin family of antiparasitic agents; isolation, structure elucidation, biosynthesis, and biological activity of the avermectins